Getting the most out of your permanent plot data - Vanclay, J.K. (1997)
A catalogue of ideas for graphical analyses of growth data is presented, in the hope of stimulating the more imaginative analyses. Graphs can be particularly revealing, because the human eye is good at detecting patterns. Suggestions are given to make graphs more effective, and analyses more insightful.